PENDAMPINGAN PENGEMBANGAN DAN KOMERSIALISASI PRODUK INTERIOR BERBAHAN BAKU LIMBAH KAIN DI BANK SAMPAH GULON ASRI, JEBRES, SURAKARTA - Alimin, Nurhayatu Nufut; Nadim, Nadim; Adisa, Hikmah Pra; Murni, Endri Sintiana; Purwandaru, Pandu; Sulistyono, If Bambang; Mulyono, Ambar (Adi Widya : Jurnal Pengabdian Masyarakat, 2024)
The trend of thrifting has exacerbated the problem of fabric waste in Indonesia. Therefore, sustainable efforts are needed, such as activating fabric waste processing activities in the community. The Gulon Asri Jebres waste bank is a place for community service activities carried out by the UNS interior design study program to develop interior products that have more value for fabric waste materials. This community service activity emphasizes the development of interior product designs made from fabric waste. Development activities are accompanied by lecturers and interior design students from the start of making sketches until later they become ready-to-sell products using a design thinking approach. The products produced include chairs, laundry baskets, curtains, cushions, and plant hangings.